Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Kemandirian Keuangan Pemerintah Daerah: Studi Kasus Pada Pemerintah Provinsi di Indonesia Tahun 2018-2021 - Lulu Syifa Fadhila; Dewi Susilowati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aim to determine the impact of original revenue and intergovermental transfer to regional government financial performance.The populations are proviancial goverments in Indonesia in 2018-2021.The method used in this research was descriptive method by using empirical study. Technique of collecting data was conducted through secondary data obtained from document research. The data analysis technique is panel data regression with spss v.25. The result of this study are (1) Original revieanue has a positive effect to regional government financial performance; (2) Intergovermental transfer has a negative effect to regional government financial performance; and (3) Original revenue and intergovermental transfer have a positive effect to regional government financial performance.